Greater knee muscular strength during high velocity movement among practitioners of taekwondo - Fong, S. S. M.; Ng, S. S. M.; Chow, L. P. Y.; Chow, C. C.; Chung, L. M. Y. (Journal of Combat Sports and Martial Arts, 2013)
Introduction. Taekwondo (TKD) training places emphasis on fast and high kicks. Thus, the practice of TKD may be beneficial for strengthening lower-limb muscles in young people. The objective of our study was to compare isokinetic knee muscular strength between TKD practitioners and control participants during movement at different velocities. Material and methods. Sixty-eight TKD practitioners and 72 age- and sex-matched control participants were enrolled in our study. Body height and weight were measured using a mechanical scale with an attached height rod. Measurements of the iso-kinetic peak torque for knee extension and flexion were recorded at 60°/s, 180°/s, and 240°/s using a Cybex Norm isokinetic dynamometer. Results. Results revealed that the isokinetic peak-torque values for knee extension and flexion at 240º/s were 11.5% and 16.6% higher, respectively, in the TKD group than in the control group (P <0 .05). No significant intergroup difference in knee muscular strength was found at the lower angular velocities (60°/s and 180°/s). Conclusions. The practice of TKD may be beneficial for improving knee muscular strength in adolescents, especially with regard to the repetition of high-velocity movements.